Acidentes de trabalho: custos previdenciários e dias de trabalho perdidos Occupational accidents: social insurance costs and work days lost - Vilma Sousa Santana; José Bouzas Araújo-Filho; Paulo Rogério Albuquerque-Oliveira; Anadergh Barbosa-Branco (Universidade de São Paulo, 2006)
OBJETIVO: Estimar a contribuição de benefícios concedidos por acidentes de trabalho dentre o total de benefícios relacionados com a saúde da Previdência Social, focalizando os custos conforme o tipo de benefício, e o impacto sobre a produtividade relativa a dias perdidos de trabalho. MÉTODOS: Utilizam-se registros dos despachos de benefícios do Sistema Único de Benefícios do Instituto Nacional de Seguridade Social da Bahia, em 2000. Acidentes de trabalho foram definidos com o diagnóstico clínico para Causas Externas, Lesões e Envenenamentos (SS-00 a T99) da Classificação Internacional de Doenças 10ª Revisão, e o tipo de benefício que distingue problemas de saúde ocupacionais e não ocupacionais. RESULTADOS: Foram estudados 31.096 benefícios concedidos por doenças ou agravos à saúde, dos quais 2.857 (7,3%) eram devidos a acidentes de trabalho. Maiores proporções foram estimadas entre os trabalhadores da indústria da transformação e construção/eletricidade/gás, 18% do total dos benefícios. Os custos com os benefícios para acidentes de trabalho foram estimados em R$8,5 milhões, com aproximadamente meio milhão de dias perdidos de trabalho no ano. CONCLUSÕES: Apesar do conhecimento de que esses dados são sub-enumerados, e restritos aos trabalhadores que conseguiram receber benefícios relacionados com a saúde, os achados revelam o grande impacto sobre a produtividade e o orçamento do Instituto Nacional de Previdência Social de agravos reconhecidos como evitáveis, reforçando a necessidade de sua prevenção. OBJECTIVE: To estimate the proportion of occupational accident benefits granted within the total for health-related social security benefits, viewing the costs according to benefit type and the impact on productivity according to work days lost. METHODS: Records of benefit decisions from the National Benefits System of the National Social Security Institute for the State of Bahia in 2000 were utilized. Occupational accidents were defined in accordance with the clinical diagnoses of External Causes, Injuries and Poisoning (SS-00 to T99) of the International Classification of Diseases, 10th Revision, and with the benefit type, which distinguishes between occupational and non-occupational health problems. RESULTS: A total of 31,096 benefits granted due to illnesses or health problems were studied. Of these, 2,857 (7.3%) were caused by work accidents. Greater proportions were found among workers in the manufacturing, construction, electricity and gas industries, accounting for 18% of the total benefits. The costs of occupational accident benefits were estimated to be R$8.5 million, with around half a million work days lost during the year studied. CONCLUSIONS: Despite the fact that these data are under-reported and are restricted to workers who were able to receive health-related benefits, the findings reveal that avoidable health problems have a major impact on productivity and on the budget of the National Social Security Institute, thereby reinforcing the need for their prevention.